Transformation activity in ultrafine grained pseudoelastic NiTi wires during small amplitude loading/unloading experiments - Pelegrina, Jorge Luis (2015)
Martensitic phase transformations were studied in ultrafine grained Ni-rich pseudoelastic NiTi wires during cyclic deformation under small imposed strain amplitudes. Small strain variation tests were complemented by a thermographic analysis of the emerging temperature distributions in the specimens. The characteristics of the observed thermal profiles result from the specific phase transitions which take place at different stress levels. Homogeneous temperature changes, corresponding to a non-localized transformation activity along the specimen length, were observed throughout the whole range of applied stresses, starting from values as low as 100 MPa. This behavior is in line with previous literature reports for the stress-induced transformation from B2 austenite to R-phase as long as the critical stress for B19′ martensite formation is not reached. In the present study, similar type of transformation activity could also be demonstrated at higher strains/stresses, even after the stress induced transformation to B19′ was apparently completed. These findings suggest that transformation activity involving the B2 phase is present throughout the whole pseudoelastic stress-strain cycle; i.e., it is not restricted to the initial loading portion. Finally, non-localized transformation to or from B19′ was identified during small amplitude strain variations in the plateau-like coexistence ranges of the pseudoelastic cycle.